1985
DOI: 10.1111/j.1365-2125.1985.tb05115.x
|View full text |Cite
|
Sign up to set email alerts
|

Enoxacin decreases the clearance of theophylline in man.

Abstract: In patients treated concurrently with theophylline and enoxacin, a new broad‐spectrum antibacterial agent of the quinolone class, unexpectedly high plasma theophylline concentrations were measured. In part I of this study, daily plasma theophylline concentrations were measured in 14 patients. The mean +/‐ s.d. theophylline concentrations increased from 8.5 +/‐ 2.8 micrograms ml‐1 prior to enoxacin to a maximum of 21.7 +/‐ 7.8 micrograms ml‐1 during coadministration. In part II, six of these patients received a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0

Year Published

1986
1986
2001
2001

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(40 citation statements)
references
References 17 publications
3
37
0
Order By: Relevance
“…The in vivo experiments in this study showed that ENX markedly and NFLX slightly prolonged the T1 /2 of theophylline in rats, but OFLX did not affect it. Many investigators have reported a similar result in human sub jects, that ENX markedly raised the plasma theophylline concentration and prolonged its T1 /2, whereas NFLX and OFLX had little or no effect on the pharmacokinetics of theophyl line (1)(2)(3)(4)(5)(6)(7)(8). Sekine et al (12) and Okazaki et al (26) have shown similar results in rats con cerning ENX and OFLX.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…The in vivo experiments in this study showed that ENX markedly and NFLX slightly prolonged the T1 /2 of theophylline in rats, but OFLX did not affect it. Many investigators have reported a similar result in human sub jects, that ENX markedly raised the plasma theophylline concentration and prolonged its T1 /2, whereas NFLX and OFLX had little or no effect on the pharmacokinetics of theophyl line (1)(2)(3)(4)(5)(6)(7)(8). Sekine et al (12) and Okazaki et al (26) have shown similar results in rats con cerning ENX and OFLX.…”
Section: Discussionsupporting
confidence: 61%
“…Since then, many investigators have demonstrated that ENX raises the plasma theophylline concentration and prolongs its elimination half-life (T1 /2). In contrast, other new quinolones, such as norfloxacin (NFLX) and ofloxacin (OFLX), have no or only a slight effect on the pharmacokinetics of theophyl line (2)(3)(4)(5)(6)(7)(8). It appears that the increase in the plasma theophylline concentration is due to a reduced metabolic clearance of theophylline in the liver induced by ENX, while NFLX and OFLX seem to have little effect on drug metabolizing activity in the liver.…”
Section: Acceptedmentioning
confidence: 80%
See 2 more Smart Citations
“…Further investigation into this increase in plasma theophylline concentrations showed that neither theophylline protein binding nor theophylline renal clearance were influenced by the enoxacin co-medication; it was therefore concluded that the interaction mechanism might be a decreased theophylline metabolic clearance (Wijnands et al, 1985b).…”
Section: Introductionmentioning
confidence: 99%